The Influence of Teacher Performance and Learning Motivation on Academic Achievement of 5th Grade Elementary School Students in Tomohon Tengah District - Susan Wanda Ticoalu; Mozes M. Wullur; Widdy H.F. Rorimpandey (PT. AHLAL PUBLISHER NUSANTARA, 2026)
Purpose: This study aims to examine the influence of teacher performance and learning motivation on the academic achievement of 5th-grade elementary school students in Tomohon Tengah District, either partially or simultaneously. Methodology: A quantitative approach with a survey method was employed. The population consisted of 141 fifth-grade students from seven elementary schools in Tomohon Tengah District. Using the Taro Yamane formula with a 10% precision level, a sample of 59 students was selected through proportional random sampling. Data were collected using validated and reliable questionnaires measured on a Likert scale. Data analysis included descriptive statistics, normality tests, linearity tests, simple linear regression, multiple linear regression, and correlation analysis using SPSS version 25.0. Findings: The results revealed that: (1) Teacher performance has a significant positive influence on student academic achievement (r = 0.788, R² = 62.1%, F = 93.415, p < 0.05); (2) Learning motivation has a significant positive influence on student academic achievement (r = 0.753, R² = 56.6%, F = 74.485, p < 0.05); (3) Teacher performance and learning motivation simultaneously have a significant influence on academic achievement (R = 0.846, R² = 71.5%, F = 70.263, p < 0.05). Teacher performance contributed a larger standardized coefficient (β = 0.516) compared to learning motivation (β = 0.410).Originality/Value: This research provides empirical evidence regarding the combined contribution of external factors (teacher performance) and internal factors (learning motivation) in shaping elementary school students' academic achievement in the context of Tomohon Tengah District. The findings offer practical implications for teachers, schools, and parents in improving educational quality at the elementary level.Keywords: Teacher Performance, Learning Motivation, Academic Achievement, Elementary School, Quantitative Study